PEMBERDAYAAN KELOMPOK PEREMPUAN BERBASIS BADAN USAHA MILIK DESA DI DESA PONGGOK, KABUPATEN KLATEN - Winarti, Safitri Endah; Herawati, Herawati; Sidik, Fajar (Puslitbangkesos Kementerian Sosial RI, 2020)
This article aims to explain the constraints of Family Welfare Empowerment (PKK) based on Village-Owned Enterprises (BUM Desa) in Ponggok Village, Klaten Regency. Qualitative research with a case study method approach is used to explore problems that occur in the field. This research is motivated by the phenomenon of the establishment and development of BUM Desa after the village fund policy was set to start in 2014. Only in a few years, the number of BUM Desa has increased significantly, but many BUM Desa are unable to be active and productive in running their business. Ponggok Village has become a village of achievement and national pilot designation designated by the Central Government, so that it is used as a research location for further study. This problem is then understood using social theory theory. The study was conducted qualitatively with the case study approach method. In problem exploration activities, primary and secondary data are collected using interview, observation, and documentation techniques. Primary and secondary data obtained are then analyzed using qualitative data analysis techniques according to Miles and Huberman. Based on the results of data analysis that has been done, the research team in this study can conclude that the empowerment of BUM Desa-based women groups in developing small businesses that produce local products typical of villages and tourist villages can increase additional income for them, but the results of the business profits are still likely dominated by the parent PKK (central) rather than the women's groups fostered at the lowest level. Recommendations that can be given from this research, namely the results of the study can be used as input for improvement so that community empowerment is more targeted and accelerates village development to run more optimally from the grass roots